Mechanism of vasorelaxation induced by Tridax procumbens extract in rat thoracic aorta - Salahdeen, Hussein Mofomosara (J Intercult Ethnopharmacol, 2016)
BACKGROUND/AIM: Tridax procumbens (Linn) (Asteraceae) is one of the herbs widely distributed in many parts of the world. Its leaves have long been used for the treatment of hypertension in Nigeria. Previous studies have shown that aqueous leaves of T. procumbens extract (TPE) lowers blood pressure through endothelium-dependent and -independent mechanism in the aortic rings isolated from normotensive rats. The aim of the present study was to further investigate mechanisms of TPE-induced relaxation in the aortic artery by assessing its mechanistic interactions with nitric oxide (NO) synthase, cyclic guanosine monophosphate (cGMP), and cyclic adenosine monophosphate (cAMP). MATERIALS AND METHODS: The aortic artery isolated from healthy, young adult normotensive Wistar albino rats (250-300 g) were pre-contracted with phenylephrine (PE) (10–7 M) and KCl (60 mM) and were treated with various concentrations of aqueous extract of TPE (0.5-9.0 mg/ml). The changes in arterial tension were recorded using Ugo Basile model 7004 coupled to data capsule acquisition system model 17400. The interaction between TPE with cAMP and cGMP inhibitors was also evaluated. RESULTS: The results showed that the TPE (0.5-9.0 mg/ml) significantly (P < 0.05) reduced the contraction induced by PE in a concentration-dependent manner. The vasorelaxant effect caused by the TPE was significantly (P < 0.05) attenuated with pre-incubation of cGMP (Rp-8Br PET cGMPS) and cAMP (Rp-AMP) inhibitor, respectively. CONCLUSION: These results suggest that TPE causes vasodilatory effects in a concentration-dependent manner in the isolated rat aortic artery. The mechanism of action of TPE is complex. A part of its relaxing effect is mediated directly by blocking or modulating cGMP and cAMP.